2001
DOI: 10.1111/0022-4537.00204
|View full text |Cite
|
Sign up to set email alerts
|

Coping With Prejudice: Personal Relationship Partners as Sources of Socioemotional Support for Stigmatized Individuals

Abstract: In the present article, I consider the behavior of nonstigmatized versus stigmatized perceivers toward stigmatized target persons in personal relationships. First, I argue that nonstigmatized persons generally are less likely to enter into personal relationships with or to give affection and respect as socioemotional support to stigmatized persons than are other stigmatized persons. Second, I present a variety of facilitators and barriers to stigmatized persons' supportive function as well as factors that migh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…are more vulnerable (e.g., characterized by lower self‐esteem, more negative affect, etc.) than people with non‐concealable stigmas (Frable, Platt, & Hoey, ), which could reflect their difficulty to find similar others able to provide a precious social support (Gaines, ). In addition to these affective implications, hiding a stigma can have cognitive consequences (e.g., obsessive and intrusive thoughts, etc., Smart & Wegner, , ).…”
Section: Discussionmentioning
confidence: 99%
“…are more vulnerable (e.g., characterized by lower self‐esteem, more negative affect, etc.) than people with non‐concealable stigmas (Frable, Platt, & Hoey, ), which could reflect their difficulty to find similar others able to provide a precious social support (Gaines, ). In addition to these affective implications, hiding a stigma can have cognitive consequences (e.g., obsessive and intrusive thoughts, etc., Smart & Wegner, , ).…”
Section: Discussionmentioning
confidence: 99%
“…Both quantitative and qualitative studies have identified family disapproval and lower social support of interracial couples (Authors, 2012;Killian, 2001;Root, 2001). Interracial couples may be ostracized from their families of origin (Gaines, 2001) and actively discouraged by messages of ''concern'' about social acceptance and biracial grandchildren (Romano, 2003). There is some evidence that these relationships may be more vulnerable to dissolution (Bratter & King, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, because of their apparent tolerance toward the stigmatized, strong-tie contacts might be more readily stigmatized than weak-tie contacts (see Gaines [2001]; Snyder, Omoto, and Crain [1999]). Being casually acquainted to a stigmatized person, for example, is likely less damaging for one's social identity than being seen as that person's best friend or trusted confidant.…”
Section: The Double Edge Of Strong Tiesmentioning
confidence: 99%